What Lies Beneath the Surface? A Case Study of Citizens' Moral Reasoning with Regard to Biodiversity. (1st May 2011) - Ojala, Maria; Lidskog, Rolf
Abstract : This paper focuses on a Swedish case where a biological insecticide has been used to fight mosquitoes in order to reduce the nuisance to humans. The case concerns conflicting values regarding environmental protection. People's quality of life in the summers is placed in opposition to long-term risks to biodiversity. On the surface, the affected lay-population is one-sidedly positive about the intervention. However, interviews with citizens revealed a more complex picture, where the majority also touched upon value conflicts. At the same time, different psychological mechanisms for handling these dilemmas hindered more critical and doubtful views from being included in societal deliberations concerning the intervention. By way of conclusion, we argue that it is important to create deliberative arrangements that acknowledge the emotional and contradictory side of human nature and that encourage people to dare to voice standpoints that may be seen as uncomfortable or inconsistent.